(untitled) (Business Vision, 2025)
This research analyzes the evolution of scientific production in green supply chains and sustainable practices through a bibliometric approach. Between 2012 and 2023, a steady growth in publications was observed, reaching more than 350 articles in 2023. This increase reflects a growing interest in integrating sustainability into supply chains, driven by academic advances and funding. However, a decrease in average citations from 2019 suggests a diversification in impact due to the high volume of recent publications that have not yet accumulated sufficient citations. The analysis highlights leading authors such as Wang Y, Manna S.K. and Sengal J. for their productivity, and Mangla SK and Sarkis J. as the most influential according to their H-index. By country, China and India lead in scientific output, albeit with predominantly national focuses. In contrast, countries such as the UK and Australia stand out for their international collaborations. The main themes revolve around sustainability, environmental management and green economy, with emerging concepts such as circular economy and emissions reduction. Collaborative networks and thematic clusters reveal a multidisciplinary approach that integrates sustainability, strategic decisions and economics. The findings suggest that current research is shaping innovative approaches to address environmental, social and economic challenges. This analysis underscores the importance of global synergies and the intersection between green economy and public policy for the development of more responsible and efficient supply chains.